بعض الخصائص البيئية والبكتريولوجيه لمياه اهوار محافظة ذي قار جنوب العراق - طالب سناء (University of Thi-Qar Journal of Science, 2008)
The present study has determined some of chemical ,physical and biological factors for five marshes in Thi-Qar governorate at southof Iraq, during January- march \2007. Investigated marshes were Chibaish ,Abu-zarag, AL-hamar,ALAdel and Gurmashia Marshes.The results show that the ranges of physical and chemical factors were reported for pH , conductivity, turbidity ,DO;BOD , dissolved salts and total hardness values which they ranged between ( 7.60-8.6), (1.5-4.89) cil/cm,(14.88-33.13) NTU,(4.8 - 8 .8) mg/L,(3.0-8.7)mg/L,(913-2320)mg/L and (435-876)mg/Lrespectively.Whereas the study determined the ranges of chemical factors which were the chloride and sulfates , phosphates and nitrates alues which ranged between (331 - 592) mg/L ,(77-131) mg /L ,(8.5-29.3) mg/L and (2.0-5.8) mg/L respectively. Mean while the microbiology study included